Qashash Al-Qur'an: Fakta atau Sebatas Rekaan? - Hajma, Zelviyah Nur; Sohrah, Sohrah; Miswar, Andi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This study examines qashash al-Qur’an as part of the Qur’anic narrative that carries historical and educational values. The primary objective is to explore the characteristics, purposes, and relevance of Qur’anic stories from the perspective of ulumul Qur'an. This research employs a qualitative approach based on literature reviews, analyzing credible references, including books, scientific journals, and other academic sources. The findings reveal that qashash al-Qur’an is unique in its fragmentary, anonymous, and repetitive presentation, emphasizing profound moral messages. Furthermore, these stories serve not only as historical narratives but also as ethical guidance and a reinforcement of faith. The repetition of stories in the Qur’an reflects the beauty of its balaghah and the miraculous nature of divine revelation. These findings affirm that the Qur’anic stories are not fictional but divine revelations that remain relevant across eras. This study aims to enhance the understanding of Muslims regarding the Qur’anic values and serves as a foundation for further research on qashash al-Qur’an.